PERLUASAN DAN PEMERATAAN PENDIDIKAN DASAR: IMPLEMENTASI KEBIJAKAN SLTP TERBUKA DI KECAMATAN SAYUNG KABUPATEN DEMAK - Ngabiyanto Ngabiyanto (Universitas Sebelas Maret, 2008)
Education is human capital that will bring human to science and technologymastery. In the term of national development, especially the increasing of humanresources, it is necessary to equalize education quality, particularly basic education inthe regions that are not reached out by the education system. As an alternative ofeducation system, SLTP Terbuka is a policy of the basic education that is held to equalizeand broaden the opportunity of nine-years basic education in which its existence is sostrategic. The research conducted in SLTP Terbuka, Sayung, Demak regency, CentralJava province, purposes to describe, analyze, and interpret implementation of SLTPTerbuka as an alternative policy of the broadening and equalizing on basic education.The qualitative approach was used in this case study. Important findings could beconcluded as follows: SLTP Terbuka had given more opportunities for the students tocontinue their study after they finish their studies at elementary school. In the long term,the implementation of this policy which can change the structure of education system hasoffered various facilities, both for the pupils and their parents.